Pemberdayaan Masjid sebagai Fungsi Sosial dan Ekonomi bagi Jamaah Pemegang Saham Unit Usaha Bersama - Suryorini, Ariana (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2019)
The function of the mosque is very universal, other than in the religious field, the mosque also has other functions which include religious/worship functions, educational functions, unifying functions of the people, social functions and economic functions. Islam places the mosque in a strategic position. Considering the strategic function of the mosque, it is necessary to provide good guidance, in terms of the physical building and the aspects of its prosperity. The mosque is expected to be a center of social and economic activity for its worshipers, not just a center for worship activities. Mosque empowerment is very important because it can provide a positive perspective related to the utilization of human resources through the empowerment of mosques for the welfare of Muslims. In the economic function of the empowerment of the Sirathal Mustaqim mosque through the activities of the Joint Business Unit (UB), whose ownership is pilgrims who have equity participation or capital ownership, which they refer to as shares of the business units they run, where profits are distributed to the owners or accompanying members of the capital in a meeting of capital owner members every year. The Joint Business Unit (UB) is named UB Rejeki Barokah, whose economic function activities are very diverse, both in the retail business of kiosks, services and goods credit business.Â Fungsi masjid sangat universal, selain di bidang keagamaan, masjid juga mempunyai fungsi lain yang meliputi fungsi keagamaan/peribadatan, fungsi pendidikan, fungsi pemersatu umat, fungsi sosial dan fungsi ekonomi. Islam menempatkan masjid dalam posisi yang strategis. Mengingat fungsi masjid yang strategis maka perlu pembinaan secara baik, dari segi fisik bangunan maupun segi kegiatan pemakmurannnya. Masjid diharapkan bisa menjadi pusat aktivitas sosial dan ekonomi bagi para jamaahnya, tidak hanya menjadi pusat kegiatan ibadah saja. Pemberdayaan masjid menjadi hal yang sangat penting karena dapat memberikan perspektif positif terkait pemanfaatan sumber daya manusia melalui pemberdayaan masjid untuk kesejahteraan umat Islam. Dalam fungsi ekonomi pemberdayaan masjid Sirathal Mustaqim melalui aktivitas unit Usaha Bersama (UB), yang kepemilikannya adalah jamaah yang mempunyai penyertaan atau kepemilikan modal, yang mereka sebut seperti saham dari unit usaha yang mereka jalankan, dimana keuntungannya dibagikan kepada jamaah pemilik atau penyerta modal tersebut dalam rapat anggota Pemilik modal setiap tahunnya. Unit Usaha Bersama (UB) tersebut bernama UB Rejeki Barokah, yang aktivitas fungsi ekononominya sangat beragam, baik dalam usaha retail kios, jasa maupun usaha perkreditan barang.